2014
DOI: 10.1521/soco.2014.32.1.1
|View full text |Cite
|
Sign up to set email alerts
|

From a Different Vantage: Intergroup Attitudes Among Children from Low- and Intermediate-Status Racial Groups

Abstract: Social groups are often described as hierarchically ordered in terms of social status. Intergroup research has generally focused on the relationship between the highest-status group and a single lower-status group, leaving relationships among nondominant groups relatively unexplored. Focusing on low-status Black and intermediate-status Coloured (multiracial) South African elementary school-children, we examined the attitudes members of these two groups hold toward one another and toward a range of other locall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
92
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 38 publications
14
92
2
Order By: Relevance
“…A second reason why Cameroon is of particular interest is because it offers an interesting contrast to South Africa, where previous research on implicit racial bias has been conducted (Dunham et al., ; Newheiser, Dunham, Merrill, Hoosain, & Olson, ). That work suggested that young South African children do not have in‐group racial biases.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A second reason why Cameroon is of particular interest is because it offers an interesting contrast to South Africa, where previous research on implicit racial bias has been conducted (Dunham et al., ; Newheiser, Dunham, Merrill, Hoosain, & Olson, ). That work suggested that young South African children do not have in‐group racial biases.…”
Section: Studymentioning
confidence: 99%
“…Almost all the research on this topic has focused on individuals over 6 years of age. This work has demonstrated that implicit racial biases are robust starting at this age (Baron & Banaji, ; Dunham, Newheiser, Hoosain, Merrill, & Olson, ; Dunham et al., , ; Rutland, Cameron, Milne, & McGeorge, ). Moreover, the limited research that has been done on younger children suggests that these biases may emerge at an age substantially earlier than 6 years (Anzures, Quinn, Pascalis, Slater, & Lee, ; Dunham et al., ; Quinn et al., ; Xiao et al., ).…”
mentioning
confidence: 96%
“…For example, the Implicit Association Test (Greenwald, McGhee, & Schwartz, 1998), the most common measure of implicit attitudes in both children and adults, requires a pair of category labels and involves making dichotomous categorization decisions about individuals. To be clear, there is nothing intrinsically unreasonable about many of these decisions; indeed, we ourselves regularly make them in our own work (Dunham, Newheiser, Hoosain, Merrill, & Olson, 2014;Dunham, Srinivasan, Dotsch, & Barner, 2014). But we have begun to worry that when these decisions come to predominate, the assumptions embedded within them can become obscured by habit.…”
Section: The Focus On Discrete Categoriesmentioning
confidence: 99%
“…Even in countries with large multiracial populations, such that dichotomous conceptions of race seem inadequate, the tendency to impose discrete categories frequently still emerges through the addition of a third discrete category term that encompasses multiracial individuals, such as "Coloured" in South Africa (Dunham, Newheiser, et al, 2014;Newheiser, Dunham, Merrill, Hoosain, & Olson, 2013) and "Pardo" in Brazil (Telles, 2002). We suspect that many of the problematic aspects of dichotomous categories will also appear in these cases.…”
Section: Race As Continua Versus Categorymentioning
confidence: 99%
“…Previous research has demonstrated that IAT results are orthogonal to the prevalence of particular groups. For example, adults in the United States and Japan failed to show any preference on an American-Japanese IAT, despite the greater prevalence of Americans in the United States and Japanese individuals in Japan (Dunham, Baron, & Banaji, 2006); Black and multiracial children in South Africa showed implicit preferences for multiracial over Black despite the fact that Black people constitute about 80% of the South African population (Dunham, Newheiser, Hoosain, Merrill, & Olson, 2014); and the IAT revealed pro-female preferences despite the fact that women and men are approximately equally prevalent (Rudman & Goodwin, 2004). Given this prior work, it seems unlikely that the patterns of implicit preferences in the current study emerged as a result of the proportion of theists to non-theists in the United States.…”
Section: 1 Studymentioning
confidence: 99%